Aortic arch impingement with Salter Harris II epiphyseal fracture of the medial clavicle: A novel use of video assisted thoracoscopy - Victoria Cook; Miranda Norquay; Terence Moopanar; Peter Brady (Trauma Case Reports, 2023)
Posterior dislocation of the sternoclavicular joint (SCJ), although uncommon, can be life-threatening. Displacement of the clavicular head poses a threat to the vital structures of the mediastinum. We describe the case of a 15-year-old boy with traumatic Salter Harris II medial clavicular fracture with posterior dislocation of the metaphysis resulting in impingement of the aortic arch, left subclavian and common carotid artery, as well as partial obstruction of the brachiocephalic vein. We describe the novel use of video-assisted thoracoscopy to assist with a safe open reduction and fixation of the fracture dislocation. The case highlights the importance of computer tomography imaging for diagnosis of posterior SCJ fracture/dislocations and the early recognition of potential life-threatening complications in the mediastinum.